Effect of Service Quality and Price on Customer Satisfaction - Safirah Ramadhaniati; Evi Susanti; Arjuna Wiwaha; Isthi Wahyuning Tyas (STIE-JIC, 2020)
The determinants of customer satisfaction are service quality and price. Therefore, this study aimed to determine the effects of service quality and price on customer satisfaction. This research was conducted at a Forwarding Company, with a total sample of 78 respondents. Meanwhile, the data analysis method used was descriptive and multiple linear regression using SPSS 25. The results showed that service quality and price has a significant effect on customer satisfaction with a determination coefficient of 50%. Meanwhile, the remaining 50% is influenced by other variables, which have been widely studied. However, research in forwarding service companies is rarely conducted.